KEUNGGULAN ARBITRASE SEBAGAI FORUM PENYELESAIAN SENGKETA DI LUAR PENGADILAN - Indah Sari (JURNAL ILMIAH HUKUM DIRGANTARA, 2019)
There are two kinds of dispute settlement; a dispute could be resolved by a judicial decision (litigation) or by a non-litigation process. This non-litigation process also known as alternative dispute resolution and arbitration. This writing focused on dispute settlement by an arbitration process. This alternative resolution prefered mostly by business people to resolve their disputation for its positive characterization. Arbitration mechanism tend to be operated fastly, efficiently, and effectively, while the case handled by expertises with integrity. The objective of dispute resolution through arbitration is to bring about a win-win solution and justice for each part involved. Regulation about arbitration has been enacted by Arbitration Act No 30 Year 1999 about Arbitration and Alternative Dispute Resolution, while it has also been arrange internationally by New York Convention of 1958, Washington Convention of 1965, UNCITRAL Arbitration Rules 1976, and UNCITRAL Model Law on International Commercial 1985.  Keywords: Alternative Dispute Resolution, Arbitration, Arbiter, Arbitration Act No.30 Year 1999